"Treating him…like a piece of meat": Poor communication as a barrier to care for people with learning disabilities - Badcock, Eleanor; Sakellariou, Dikaios (Disability Studies Quarterly, 2022)
People with learning disabilities face numerous barriers accessing health and social care. Previous studies have identified that poor communication can be a significant barrier, but this has not been explored in depth. This article explores the perceptions and experiences of people with learning disabilities and their family carers regarding communication with health and social care professionals, in order to establish both the areas that they find problematic and also identify strategies that can lead to more effective communication. Five people with learning disabilities and their family carers participated in the study, sharing their experiences through the use of semi-structured and symbol exchange interviews, and pictures. Communication was an area of concern for all participants, affecting their access to health and social care. Participants reported instances of ineffective and disrespectful communication and identified a desire for professionals to use a variety of communication methods, such as gestures, touch, and images, rather than relying on verbal language alone and to treat people with learning disabilities with respect.